1991
DOI: 10.1103/physrevb.43.3020
|View full text |Cite
|
Sign up to set email alerts
|

Positive Hall coefficient observed in single-crystalNd2xCe

Abstract: The Hall coefficient RH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
77
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(86 citation statements)
references
References 18 publications
9
77
0
Order By: Relevance
“…1 However, R H and thermoelectric power gradually increase and eventually change sign to positive with further doping Ce. 2,3,4,5,6,7 Similar feature has been observed with changing the oxygen content. 4,8 In another ntype cuprate P r 2−x Ce x CuO 4+δ (PCCO), the change of R H sign with temperature 9,10,11 and doping 12 were also observed.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…1 However, R H and thermoelectric power gradually increase and eventually change sign to positive with further doping Ce. 2,3,4,5,6,7 Similar feature has been observed with changing the oxygen content. 4,8 In another ntype cuprate P r 2−x Ce x CuO 4+δ (PCCO), the change of R H sign with temperature 9,10,11 and doping 12 were also observed.…”
supporting
confidence: 77%
“…Especially for x=0.025, such low temperature insulating behavior becomes obvious around 240 K, similar to the report by Onose et al 1 However, the metallic behavior can be observed in the high temperature range. For the overdoped samples, metallic behavior exists in the whole temperature range and superconductivity was observed and slightly overdoped superconducting (x∼0.17) compositions, the change of Hall coefficient sign with temperature has been reported 4,6,8,10 . The conventional single-carrier transport can not explain such behavior adequately, and two types of the carriers have to be used to explain these behaviors.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…In this cuprate, the qp contribution to the Nernst signal is large. From early Hall-effect experiments [81,82] as well as ARPES, it is known that both electron-like and hole-like bands contribute to the qp current. The presence of both bands leads to a change in sign of the normal-state Hall coefficient R H in OP crystals [81,82].…”
Section: Electron-doped Cupratementioning
confidence: 99%